2018
DOI: 10.1093/ndt/gfy216
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and treatment versus risk of infection in end-stage renal disease patients under dialysis: a systematic review and meta-analysis

Abstract: High or normal serum levels of 25(OH)D and the use of vitamin D, particularly VDRA, were each associated with a lower risk of composite infection in long-term dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Furthermore, there is some evidence to suggest an anti-infective effect of vitamin D in specific patient groups, such as patients with chronic kidney disease (CKD), human immunodeficiency virus (HIV) or hepatitis C virus (HCV) infection. Among patients with CKD receiving dialysis, a case-control study indicated that the risk of herpes zoster reactivation was significantly lower in those who received vitamin D supplementation15; another meta-analysis also showed that patients with CKD with higher or normal serum vitamin D levels had a lower risk of infection 16. Among HIV-infected patients, lower serum vitamin D levels were also associated with a higher risk of clinical progression to AIDS and all-cause mortality in a cohort study,17 while vitamin D supplementation did not affect mortality, CD4 cell count or viral load 18.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is some evidence to suggest an anti-infective effect of vitamin D in specific patient groups, such as patients with chronic kidney disease (CKD), human immunodeficiency virus (HIV) or hepatitis C virus (HCV) infection. Among patients with CKD receiving dialysis, a case-control study indicated that the risk of herpes zoster reactivation was significantly lower in those who received vitamin D supplementation15; another meta-analysis also showed that patients with CKD with higher or normal serum vitamin D levels had a lower risk of infection 16. Among HIV-infected patients, lower serum vitamin D levels were also associated with a higher risk of clinical progression to AIDS and all-cause mortality in a cohort study,17 while vitamin D supplementation did not affect mortality, CD4 cell count or viral load 18.…”
Section: Introductionmentioning
confidence: 99%
“…At a cellular level, some studies have shown that vitamin D regulates the production of the antimicrobial peptide cathelicidin [ 10–13 ], and 1 study indicated that vitamin D supplementation was associated with a decrease in HSV-1 viral load and mRNA expression in HSV-1-infected cells [ 14 ]. In addition, among epidemiological studies, a meta-analysis showed that the risk of infection was lower in chronic kidney disease patients with normal or higher serum vitamin D levels [ 15 ], and another meta-analysis using original patient data from 25 randomized controlled trials showed that people receiving vitamin D supplementation had a lower risk of respiratory tract infection [ 16 ].…”
mentioning
confidence: 99%
“…This result indicates that the fear of potential rejection or death after transplantation could invalidate the perception of having control over one’s life and goals, thus decreasing resilience. A recent review showed how the post-transplant phase is gripped by the fear of rejection, of possible infections, or return to dialysis despite the transplant [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%